A method for detecting candida species in a specimen by polymerase chain reaction. - Chong, Pei Pei; Mohammed Harmal, Nabil Saad; Jamal, Farida; Sekawi, Zamberi (2011)

(untitled)
The present invention relates to a method for detecting Candida species in a specimen, comprising the steps of extracting nucleic acid from the specimen; performing polymerase chain reaction on the extracted nucleic acid using DNA primers for amplification of targeted nucleic acid sequence; detecting the amplified nucleic acid for each Candida species; characterized in that, in a single reaction, the DNA primers consist of: SEQ ID NO. 1 and SEQ ID NO. 2 or their complements for amplifying nucleic acid from Candida albicans; SEQ ID NO.3 and SEQ ID NO. 4 or their complements for amplifying nucleic acid from Candida glabrata; SEQ ID NO. 5 and SEQ ID NO. 6 or their complements for amplifying nucleic acid from Candida parapsilosis; SEQ ID NO. 7 and SEQ ID NO. 8 or their complements for amplifying nucleic acid from Candida tropicalis.